Status Hematologis Broiler Yang Diberikan Tepung Sangrai Biji Asam Tanpa Kulit - Maria Tanewo; Agustinus Paga; Bambang Hadisutanto (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
This research was conducted in Kupang State Agricultural Polytechnic, Prodia Clinical Laboratory, feed Chemical Laboratory of Animal Husbandry Faculty, and the Gadjah Mada University of from May 6 th until June 7 th , 2013. The aims of this resear ch was to determine the effect of skinless roasted tamarind seeds meal on hematology parameters in broiler chicken. The aims of this research was to determine the effect of skinless roasted tamarind seeds meal on hematological parameters and the level of skinless roasted tamarind seeds meal consumption in broiler chicken which can affect hematological parameter. This research used completely randomized design with 4 tr eatments and 6 replications. The treatments were basal ration without skinless roasted tamarind seeds meal (R0), 95% basal ration + 5 % meal of skinless roasted tamarind seeds meal (R1), 90 % basal ration + 10 % skinless roasted tamarind seeds meal (R2), 8 5 % basal ration + 15 % skinless roasted tamarind seeds meal (R3). The measured variables were the number of erythrocyte, hemoglobin level, hematocrit value, level of LDL, and HDL cholesterol, and triglyceride. The variants analysis to the number of erythr ocyte, hemoglobin level, and haematocrit value indicated that skinless roasted tamarind seeds meal had no significant effect to broiler (P>0.05). The level of LDL cholesterol from R0 and R1 had no significant difference. The R1, R2, and R3 treatments had s ignificant effect (P<0.01) on the LDL cholesterol of broiler. HDL cholesterol and triglycerida showed that the skinless roasted tamarind seeds meal had no significant effect (P>0.05).